The use of bio-telemetry for studying squirrel population dynamics and behavior - (:unkn) unknown (My University, 1969)
A full understanding of the ecology and behavior of any animal requires a knowledge of the animal's movements. Historically, data from natural events involving any animal under natural conditions have been obtained from such methods as trapping, marking, recapture and visual observations. In the 1950's and early 1960's however, major breakthroughs in data gathering techniques were made when biologists began developing telemetering devices with which to monitor animal movement and to a limited degree, physiological parameters. Wild animals were being tracked for days, weeks and even months, continuously telemetering such events as temperature, daily and seasonal movement patterns, dispersal and behavior. Radio-telemetry, may be defined as the use of a miniature radio transmitter attached to a free roaming, wild animal, without use of restraining harnesses or wires, and capable of emitting a signal at a given frequency, which when received by a remote receiving station provides continuous data of a specific nature.
Keywords: radio-telemetry; gray squirrel; fox squirrel; red squirrel